The Role Of Communication In The Management Function - Khaerunnisa (Business Finence Analyst Co.,, 2024)
The role of communication in management is discussed in this study. In management, the main purpose of communication is to interact well so that people can understand and understand how to communicate with others. This research uses a literature study that uses qualitative descriptive analysis. According to the research results, communication is an important tool in management to support organizational governance. Limited resources can be overcome by cooperation and utilization of technology. So, communication is an important part of management as it helps achieve organizational goals and improve performance. According to this study, improving management communication through training and creative strategies is essential to address the dynamics of management communication